Charting the Future of K-Pop: Navigating Globalization, Technological Innovations, and Cultural Dynamics in the Next Five Years - Raden Aswin Rahadi; Raden Bayuningrat Hardjakaprabon; Atika Fatka Raihani; Alya Indira Putri; Kurnia Fajar Afgani (Integrasi Sains Media, 2024)
This research explores the future trends of K-pop by analyzing the genre's trajectory in the context of globalization, technological innovations, cultural dynamics, and sustainability. The study provides a comprehensive understanding of the factors influencing K-pop's global expansion and the implications for various stakeholders, including music industry professionals, cultural analysts, and scholars of global pop culture. Through a descriptive and analytical research design, utilizing secondary data from existing literature, online resources, and industry reports, the study identifies key themes such as cultural hybridization, technological advancements, fan engagement, and ethical practices. The findings reveal that K-pop's success is driven by its ability to blend diverse cultural elements, leverage digital platforms and VR/AR technologies, foster participatory fan culture, and adopt sustainable practices. These insights offer theoretical, managerial, and practical implications for the future of the K-pop industry, highlighting the need for an integrative approach to understanding its global impact and sustainability.